VEEMEE : ARCHITECTURE DESIGN OF WEBSITE FOR 3D VIRTUAL SHOW - Kusumawati, Yudhistya Ayu; Liemantara, Nyssa Averina (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2022)
In the pandemic, the stress level due to the covid- 19 outbreak has increased. Now the entertainment industry is required to provide a variety of entertainment so that people's stress levels will reduce. The impact of high-stress levels can lead to social, economic issues. Therefore stress and mental illness need to be solved immediately. This research aims to reduce people's stress levels because of the covid-19 outbreak. To achieve that aim, the researcher presents a solution in the form of an application and website of a virtual concert that will be held in 3D.  The target to be achieved in this research is that this media is expected to reduce people's stress levels and develop entertainment in the music industry. In developing this research, the researcher conducted design thinking research and data collection methods by questionnaire. Although the solution provided is in the form of a website, it is possible to be developed into an application.